Short-term maximal-intensity work limitation factors analysis - Chikov, A. E.; Medvedev, D. S.; Chikova, S. N. (Theory and Practice of Physical Culture, 2019)
The main physiological factors limiting the implementation of short-term work of maximum intensity include the possibilities of energy supply for muscle activity and the possibility of neuromuscular transmission of efferent and afferent impulses.